The Applicability of Environmental and Economic Parameters of Microsimulation Traffic Modeling in the Evaluation of Intersection Reconstruction Solutions (Proceedings of Faculty of Civil Engineering, 2023)
Transport infrastructure designers are faced with the demanding task of balancing the conflicting goals of transport infrastructure development according to traffic demand andreducing the negative effects of the system operationalization with their solutions. This paper analyzes the applicability of microsimulation traffic modeling for the analysis of ecological and economic parameters, which, along with functional parameters, are included in the standard criteria for the evaluation of various solutions for the construction and reconstruction of traffic infrastructure. The case study was made on the example of the reconstruction of an intersection in the urban traffic network of the city of Osijek. The results show the applicability of microsimulations for the evaluation of ecological and economic parameters in the evaluation of variant solutions for the reconstruction of the intersection, and the numerical indicators show that air pollution from traffic can be reduced by improving the functional indicators of intersections.
Keywords: intersection reconstruction; microsimulations; air pollution; fuel consumption